2012
DOI: 10.1167/iovs.12-9505
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of the Proteasome Inhibitor Bortezomib on Endotoxin-Induced Uveitis in Rats

Abstract: PURPOSE. We evaluated the anti-inflammatory effect of bortezomib (Velcade), a proteasome inhibitor, on endotoxin-induced uveitis (EIU) in rats and lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. METHODS. EIU was induced by footpad injection of LPS intoLewis rats. MG-132 (10 mg/kg), or high-dose (0.2 mg/kg) or low-dose (0.05 mg/kg) bortezomib was given 30 minutes before LPS injection in each treatment group. The rats were sacrificed 24 hours later to observe the inflammatory response in tissues. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
(53 reference statements)
1
26
0
2
Order By: Relevance
“…45 Notably, activation of β 5i chymotrypsin-like activity has been recently reported to be involved in the generation and sustainment of an inflammatory environment, 11, 12, 48 whereas the use of inhibitors of this activity, such as bortezomib, has been described in many cancer therapies, 49, 50 neurodegenerative disorders 51 and other chronic inflammatory conditions. 52 We also observed that bortezomib completely restores the levels of the cytokines and inflammatory mediators induced by ethanol in WT brain cortices, thus corroborating the role of ethanol in UPS impairment.…”
Section: Discussionsupporting
confidence: 74%
“…45 Notably, activation of β 5i chymotrypsin-like activity has been recently reported to be involved in the generation and sustainment of an inflammatory environment, 11, 12, 48 whereas the use of inhibitors of this activity, such as bortezomib, has been described in many cancer therapies, 49, 50 neurodegenerative disorders 51 and other chronic inflammatory conditions. 52 We also observed that bortezomib completely restores the levels of the cytokines and inflammatory mediators induced by ethanol in WT brain cortices, thus corroborating the role of ethanol in UPS impairment.…”
Section: Discussionsupporting
confidence: 74%
“…15,16 Thus, we asked whether NF-jB signaling is involved in the doxycycline-mediated inhibition of peritoneal macrophages. We found that stimulation of macrophages with LPS increased phosphorylated NF-jBp65 protein expression, whereas doxycycline treatment significantly inhibited phos- phorylated NF-jBp65 expression in macrophages (Fig.…”
Section: Doxycycline Inhibits the Release Of Proinflammatory Mediatormentioning
confidence: 99%
“…It is approved by the FDA for use in the treatment of multiple myeloma [33]. We have demonstrated that bortezomib had anti-inflammatory effects in endotoxin-induced uveitis of rats in a previous study [34]. Concerning retinal IR injury, we hypothesized that bortezomib could inhibit the activation of NF-κB and associated inflammatory mediators, alleviate oxidative stress in the retina and reduce retinal neuron death and ganglion cell apoptosis.…”
Section: Introductionmentioning
confidence: 95%